ANALYSIS OF FACTORS RELATED TO WORKFATIGUE IN LOADING AND UNLOADING WORKERSAT MANADO PORT - Pingkan Pinontoan; Feiby J. Umboh, Conny Toliu, Quinthia Manitik, Veronika Takahegesang (CV. Adiba Aisha Amira, 2025)
Being exposed to various hazards during loading and unloading activities during high operations is very risky for occupational safety and health. As a result, there must be safety equipment for every loading and unloading activity. Age, length of service, nutritional status, and work shifts are factors that contribute to fatigue of loading and unloading workers, and activities that require a lot of action pose various risks to occupational safety and health. To determine the relationship between age, length of service, nutritional status and work fatigue in loading and unloading workers at the port of Manado. Analytical observational research with a cross sectional study approach. There is a significant relationship between age, length of service, nutritional status and work fatigue in loading and unloading workers at Manado port in 2020 with p value = 0.000. There is no significant relationship between work shifts and work fatigue among loading and unloading workers at Manado port in 2020 with p value = 0.583